Mechanical-activated digital microfluidics with gradient surface wettability. Issue 2 (12th December 2018) - Qi, Lin; Niu, Ye; Ruck, Cody; Zhao, Yi
Abstract : Long-distance droplet motion and selective droplet manipulation on repeated hydrophobic surface patterns with gradient wettability by in-plane cyclic vibration. Abstract : This paper reports a simple yet effective droplet manipulation approach that can displace aqueous droplets over a long distance within the working plane. Repeated patterns with surface gradient wettability were created on a super-hydrophobic surface by laser irradiation. Aqueous droplets as small as 2 μL are moved on the patterns over a long distance under in-plane symmetric cyclic vibration. Typical droplet manipulation actions including droplet movement along a pre-determined trajectory, droplet mixing, and selective movement of multiple droplets were successfully demonstrated. Biochemical detection using this approach was demonstrated via a bicinchoninic acid (BCA) assay. This approach allows for long-distance droplet movement and simultaneous manipulation of multiple droplets without sacrificing the manipulation efficiency or increasing the cross-contamination risk. The device can be fabricated outside cleanrooms and operated without special equipment. It provides a solid technical basis for developing the next generation of affordable open channel microfluidic devices for various applications.